2006
DOI: 10.1093/humrep/del391
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of estrogen receptor alpha gene AGATA haplotype and SNP12 in European populations: potential protective effect for cryptorchidism and lack of association with male infertility

Abstract: BACKGROUND: A specific haplotype (AGATA) in the estrogen receptor alpha (ER1) gene was recently described as a new risk factor for cryptorchidism in the Japanese population. In this ethnic group, single-nucleotide polymorphism 12 (SNP12) was concluded to be the tag SNP for the AGATA haplotype. MATERIALS AND METHODS: A large group of patients (total number = 335) and controls (total number = 567) of two Caucasian populations were analysed for the AGATA haplotype and SNP12 to verify whether this genetic variant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
2
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 17 publications
2
38
2
3
Order By: Relevance
“…In the JPN study group, five SNPs in the 3 0 region of the ESR1 gene (the AGATA allele) were found to be overrepresented in cryptorchid patients in comparison with controls (34.0 versus 21.3%), and homozygosity for this variant was found only in patients with undescended testes. 42 By contrast, in the ITA study population, the AGATA haplotype was found to be associated with a reduced risk of CO. 43 However, a rs5000770-rs3757824 interaction to susceptibility of CO was observed in the combined analysis of these two study groups. This interesting observation might explain partly the possible genetic effects masked by different gene-gene interaction leading to the controversial results in association studies, although further studies are necessary to confirm our findings in different ethnic groups.…”
Section: Discussionmentioning
confidence: 92%
“…In the JPN study group, five SNPs in the 3 0 region of the ESR1 gene (the AGATA allele) were found to be overrepresented in cryptorchid patients in comparison with controls (34.0 versus 21.3%), and homozygosity for this variant was found only in patients with undescended testes. 42 By contrast, in the ITA study population, the AGATA haplotype was found to be associated with a reduced risk of CO. 43 However, a rs5000770-rs3757824 interaction to susceptibility of CO was observed in the combined analysis of these two study groups. This interesting observation might explain partly the possible genetic effects masked by different gene-gene interaction leading to the controversial results in association studies, although further studies are necessary to confirm our findings in different ethnic groups.…”
Section: Discussionmentioning
confidence: 92%
“…On the contrary, patients with deletions of both USP9Y and DBY seem to invariably demonstrate azoospermia with a testicular histology of SCOS [17,49]. Deletion of the USP9Y gene can additionally cause azoospermia, oligozoospermia, or oligoasthenozoospermia [15,50].…”
Section: The Azfa Regionmentioning
confidence: 99%
“…In humans, ESR1 has been suggested to be an associative gene for cryptorchidism [13,14]. However, the findings have not been consistent among independent multiracial groups.…”
Section: Discussionmentioning
confidence: 95%
“…In dogs, no causative or associated genes for CO have been identified according to the reports available to date. Previously, Wende et al [28] compared the coding region of calcitonin gene-related peptide gene (CGRP) between cryptorchid and normal dogs, but no mutations or polymorphisms were identified.In humans, ESR1 has been suggested to be an associative gene for cryptorchidism [13,14]. However, the findings have not been consistent among independent multiracial groups.…”
mentioning
confidence: 95%